Cover Picture: The TEAD4–YAP/TAZ Protein–Protein Interaction: Expected Similarities and Unexpected Differences (ChemBioChem 10/2013). Issue 10 (1st July 2013) - Hau, Jean Christophe; Erdmann, Dirk; Mesrouze, Yannick; Furet, Pascal; Fontana, Patrizia; Zimmermann, Catherine; Schmelzle, Tobias; Hofmann, Francesco; Chène, Patrick
Abstract : The cover picture shows a schematic view of the interaction between the YAP and TAZ co‐activators with a TEAD transcription factor. TEAD transcription factors are key elements of the Hippo pathway, which is deregulated in various types of cancers. YAP and TAZ share a high sequence homology and bind with similar affinity at the same site on the TEAD surface. However, this apparent similarity conceals differences in the ways in which both co‐activators interact with TEAD. On p. 1218 ff., P. Chène et al. depict the similarities and differences of the TEAD4–YAP/TAZ protein–protein interaction.